Discovery of benzamide-hydroxypyridinone hybrids as potent multi-targeting agents for the treatment of Alzheimer's disease. (1st January 2021) - Jiang, Xiaoying; Guo, Jianan; Zhang, Changjun; Gu, Jinping; Zhou, Tao; Bai, Renren; Xie, Yuanyuan
Abstract: A novel class of benzamide-hydroxypyridinone (HPO) derivatives were innovatively designed, synthesised, and biologically evaluated as potential multitargeting candidates for the treatment of Alzheimer's disease (AD) through pharmacophores-merged approaches based on lead compounds 18d, benzyloxy phenyl analogs, and deferiprone (DFP). These hybrids possessed potent Monoamine oxidase B (MAO-B) inhibition as well as excellent iron chelation, with pFe 3+ values ranging from 18.13 to 19.39. Among all the compounds, 8g exhibited the most potent selective MAO-B inhibitor (IC50 = 68.4 nM, SI = 213). Moreover, 8g showed favourable pharmacokinetic properties and had great potential to penetrate the BBB in silico and PAMPA-BBB assay. Molecular modelling showed that 8g could adopt an extended conformation and have more enhanced interactions with MAO-B than 18d . In vitro and in vivo assays demonstrated that 8g remarkably resisted Aβ-induced oxidation and ameliorated cognitive impairment induced by scopolamine. Taken collectively, these results suggest that compound 8g is a potential multifunctional candidate for anti-AD treatment.